Extraction of essential oil from patchouli leaves using microwaveassisted hydrodistillation and hydrodistillation methods - Sangeethavani, Sundarajan (2020)
The use of essential oils in perfumery, pharmaceutical and cosmetics industries are increasing in the last few decades. The existing conventional methods such as hydrodistillation (HD) and steam distillation have various disadvantages such as long extraction time, high energy use, high operational cost and release of toxic wastes to the environment. In this study, the efficiency of microwave-assisted hydrodistillation (MAHD) over conventional HD in the extraction of essential oil from Patchouli (Pogostemon cablin) leaves were investigated. Three major parameters namely extraction time, volume of solvent and microwave power levels were evaluated in oil extraction for MAHD while volume of solvent and extraction time were studied for HD using onefactor-at-a-time (OFAT) experiments. In comparison between both MAHD and HD methods, MAHD showed shorter extraction time to obtain optimum yield where 23.33 mg/g of essential oil obtained through MAHD while 9 mg/g of oil obtained through conventional method for 45 minutes of extraction when using 360ml of solvent. The parameters used in OFAT were further optimized using Response Surface Methodology (RSM). The optimal conditions to produce maximum yield of 61.5 mg/g patchouli essential oil using MAHD were 440.71 W and 383.89 ml of solvent for 75 minutes of extraction while when using conventional method, only can yield maximum of 35 mg/g of patchouli oil for 75 minutes of extraction and 300 ml of solvent which is less amount compared to MAHD. Gas Chromatography-Mass Spectrometry (GC-MS), Fourier transform infrared transmission (FTIR) and Liquid chromatography–mass spectrometry Quadrupole Time of Flight (LC–MS/QTOF) analyses were employed to identify and characterize the bioactive compounds in the patchouli essential oil. FTIR bands at 3293 cm-1 for both MAHD and HD related to alcohol group show the abundance of patchouli alcohol in the oil. Moreover, 29 compounds were identified in MAHD extract while 27 compounds were found in HD extract. Besides, LC-MS/QTOF analysis indicated the presence of tannins, phenolic alkaloids, flavonoids, sesquiterpenoids lactones and triterpenoids in the patchouli oil. MAHD is a good and promising method to extract essential oils from plants because it consumes less energy and yield high amount of patchouli oil at shorter extraction time.